1984
DOI: 10.1085/jgp.84.3.403
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidence for acidic, basic, and neutral amino acid olfactory receptor sites in the catfish.

Abstract: Electrophysiological experiments indicate that olfactory receptors of the channel catfish, Ictalurus punctatus, contain different receptor sites for the acidic (A), basic (B), and neutral amino acids ; further, at least two partially interacting neutral sites exist, one for the hydrophilic neutral amino acids containing short side chains (SCN), and the second for the hydrophobic amino acids containing long side chains (LCN) . The extent of cross-adaptation was determined by comparing the electro-olfactogram (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
112
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(119 citation statements)
references
References 49 publications
7
112
0
Order By: Relevance
“…Some interspecific variability in the relative effectiveness of the 20 amino acids tested at 10 -4.2 moll -1 was observed but the neutral amino acids, such as alanine, serine and methionine, were generally highly stimulatory (Table3). Neutral amino acids were previously demonstrated to be especially potent stimuli for a few elasmobranch species and for teleost fishes (Caprio and Byrd, 1984;Silver, 1979;Tricas et al, 2009;Zeiske et al, 1986). Tricas et al (Tricas et al, 2009) found that the response of scalloped hammerhead sharks to cysteine was about twice that for alanine; however, cysteine was a less effective stimulus for the five species we tested (44-75% of alanine), which included another sphyrnid species.…”
Section: Discussionmentioning
confidence: 99%
“…Some interspecific variability in the relative effectiveness of the 20 amino acids tested at 10 -4.2 moll -1 was observed but the neutral amino acids, such as alanine, serine and methionine, were generally highly stimulatory (Table3). Neutral amino acids were previously demonstrated to be especially potent stimuli for a few elasmobranch species and for teleost fishes (Caprio and Byrd, 1984;Silver, 1979;Tricas et al, 2009;Zeiske et al, 1986). Tricas et al (Tricas et al, 2009) found that the response of scalloped hammerhead sharks to cysteine was about twice that for alanine; however, cysteine was a less effective stimulus for the five species we tested (44-75% of alanine), which included another sphyrnid species.…”
Section: Discussionmentioning
confidence: 99%
“…Responses were normalized by the response to L-arginine at 1×10 −5 mol l −1 (Siefkes and Li, 2004). The specificity with which P. marinus detected conspecific and heterospecific odours was determined using cross-adaptation experiments (Caprio and Byrd, 1984). Cross-adaptation experiments record the responses to a stimulus while the epithelium is saturated with a second stimulus (the adapting stimulus).…”
Section: Electro-olfactogram Responses To Male Odoursmentioning
confidence: 99%
“…If the 'test' and 'adapting' odorant act through independent olfactory receptor sites, the response to the test odorant during adaptation should be unaffected, i.e. not greatly reduced, compared to the signal measured prior to adaptation (Caprio and Byrd, 1984;Cole and Stacey, 2006;Sorensen et al, 1995). In binary mixture tests, receptor sites are separate if the EOG response to a mixture of two odorants is approximately the sum of the responses to the individual odorants given alone.…”
mentioning
confidence: 99%